Evaluation of a Personal Development Program for Chilean High School Students - Lagos-San Martín, Nelly (2022)
Objective. An adaptation of a personal development program created in Spain for use in the Chilean educational context is proposed and submitted for evaluation. The idea is to provide a concrete proposal that strengthens one of the thematic axes proposed in Chile as part of adolescents’ personal development and evaluate it to determine its effectiveness. Methodology. The research design corresponds to a quasi-experimental line with pre- and post-test and control groups, calculating t-tests to determine the existence of statistical differences between the results of the initial and final evaluation of self-concept, emotional intelligence, anxiety, and self-efficacy. These constructs were measured with the Self-Description Questionnaire II, short version (SDQII-S), the Trait Meta-Mood Scale 24 (TMMS-24), the State and Trait Anxiety Scale (STAI-S), and the General Self-Efficacy Questionnaire. The sample included 182 high school students from the commune of Chillán, 88 males and 94 females (48% and 52%, respectively), aged between 14 and 17 years (M=15; SD; 1.01), who were selected by convenience, according to the criterion of accessibility. Results. The results indicate that the program shows statistically significant improvements of small and moderate magnitude in the experimental group. Conclusion. For the same reason, it can be reported that the program was positively evaluated using a satisfaction survey, so it is estimated that this proposal has been able to respond to the training needs of the Chilean educational system.